Метаболический синдром и хроническая болезнь почек с точки зрения микроальбуминурии - А. М. Минасян; К. В. Маркосян; Н. А. Гарегинян; Н. Э. Авдалбекян; И. С. Казинян (Հայաստանի ԳԱԱ)
Մետաբոլիկ համախտանիշը (ՄՀ) ներառում է ճարպակալումը, դիսլիպիդեմիան, զարկերակային հիպերտենզիան, գլյուկոզի նկատմամբ տոլեռանտության խախտումը:Metabolic syndrome includes obesity, dyslipidemia, increased blood pressure and glucose intolerance. An association between the components of metabolic syndrome and chronic kidney disease has been revealed.
Keywords: Medicine; Nephrology